Study On The Effect Of Edge Computing On Latency In Iot Applications - Saputri , Vettyca Diana; Febriani , Rizki Annisa (Jurnal Komputer Indonesia, 2024)
This article examines the effect of implementing edge computing on latency in Internet of Things (IoT) applications. Edge computing moves data processing closer to the data source to reduce latency and improve efficiency. This research compares the performance of IoT applications with and without edge computing. The results show a significant reduction in latency and an increase in application response speed.